Gabby gets it together - Fairbairn, Nathan; Msassyk (New York : Razorbill, 2022)
Best friends Gabby, Priya and Mindy create a dog walking business, and quickly learn that running a business is no walk in the park.
Ages 8-12 years.
Keywords: Graphic novels; Dogs -- Fiction; Moneymaking projects -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Graphic novels